The effect of high and low exercise intensity periods on a simple memory recognition test - Ben Rattray; Disa J. Smee (Elsevier, 2016)
Purpose: The purpose of this study was to investigate the effect of variable intensities on a simple memory recognition task during exercise. Methods: Twenty active participants took part in initial testing, a familiarization trial and then four 60 min cycling interventions in a randomized order. Interventions consisted of no exercise (control), constant exercise at 90% ventilatory threshold (constant) and 2 trials that initially mimicked the constant trial, but then included periods of high (∼90%VO2peak) and low intensities (∼50%VO2peak). Cardiorespiratory measures and capillary blood samples were taken throughout. A short tablet-based cognitive task was completed prior to and during (50 and 55 min into exercise) each intervention. Results: The exercise conditions facilitated response time (p = 0.009), although the extent of this effect was not as strong in the variable exercise conditions (p = 0.011-0.089). High intensity exercise periods resulted in some cognitive regression back towards control trial performance. Elevations in cardiorespiratory measures and periods of hypocapnia could not explain changes in cognitive performance. Conclusion: Changes in cognitive performance with variations in exercise intensity are likely to have implications for sport and occupational settings. The timing of cognitive tests to exercise intensity changes as well as use of short cognitive assessments will be important for future work.